The impacts of ECB monetary policy on Euro-area bank’s performance - Antunes, José Alberto Neves Pires (2018)
Due to the severity of the financial crisis several central banks changed their policies and adopted a more active intervention. Recurring to Large Scale Asset Purchase and quantitative easing programs in order to lessen the effects of the financial crisis. The objective of the study is to analyze the impacts of the European Central Bank monetary policy on the performance of the European banks. As the research analyses banks from the different countries of the Euro area, it enables to study the impacts and how they vary from country to country, due to the heterogeneity of the European economy. The panel consists of 1183 commercial banks from 18 Countries (Austria, Belgium, Cyprus, Estonia, Finland, France, Germany, Greece, Ireland, Italy, Latvia, Luxembourg, Malta, Netherlands, Portugal, Slovakia, Slovenia and Spain) with a time period from 2011 to 2016. To achieve the goal of the research the impacts of the Gross Domestic Product (of the different Euro-area states as measure of the wealth of the nation), the value of the European Central Bank assets as well the key interest rate (as proxies of the monetary policy) on the banking performance variables will be analyzed. This study provides public deciders with new empirical and theoretical information.